2018
DOI: 10.1105/tpc.17.01000
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor-Like Cytoplasmic Kinase STRK1 Phosphorylates and Activates CatC, Thereby Regulating H2O2 Homeostasis and Improving Salt Tolerance in Rice

Abstract: Salt stress can significantly affect plant growth and agricultural productivity. Receptor-like kinases (RLKs) are believed to play essential roles in plant growth, development, and responses to abiotic stresses. Here, we identify a receptor-like cytoplasmic kinase, salt tolerance receptor-like cytoplasmic kinase 1 (STRK1), from rice () that positively regulates salt and oxidative stress tolerance. Our results show that STRK1 anchors and interacts with CatC at the plasma membrane via palmitoylation. CatC is pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(144 citation statements)
references
References 79 publications
4
139
0
1
Order By: Relevance
“…Another gene, PDE4D, also known as STRK1, is less well researched in animals but has been identified as a gene that can improve the salt tolerance of rice (Zhou et al, ). What's more, it has been determined that sudden exposure to high altitudes can cause strokes.…”
Section: Resultsmentioning
confidence: 99%
“…Another gene, PDE4D, also known as STRK1, is less well researched in animals but has been identified as a gene that can improve the salt tolerance of rice (Zhou et al, ). What's more, it has been determined that sudden exposure to high altitudes can cause strokes.…”
Section: Resultsmentioning
confidence: 99%
“…Given the fact that the phosphorylation of BAK1 is generally necessary for its potential activation of signaling, such as BR signaling [21,22] and innate immune signaling [46,47], we speculate that high light enhances phosphorylation of BAK1 for its activity potential, which in turn phosphorylates CAT1/2/3. It is notable that in Arabidopsis after CAT3 is phosphorylated by a calcium-dependent protein kinase, the catalytic activity of CAT3 was significantly enhanced [48], and in rice, the RLCK protein STRK1 phosphorylates CatC to stimulate its activity to regulate H 2 O 2 homeostasis and improve salt tolerance [49]. Thus, our results give rise to a hypothesis that phosphorylation of CATs by BAK1 results in the activation of CATs to scavenge H 2 O 2 , consequently leading to a reduction in H 2 O 2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, studies with other proteins also showed similar phenomena. For example, catalase proteins localize in peroxisomes (Apel and Hirt, 2004); however, under salt and drought stresses, the plasma membrane proteins salt tolerance receptor-like cytoplasmic kinase1 (Zhou et al, 2018) and Calcium Protein Kinase8 (Zou et al, 2015) interact with, phosphorylate, and activate Catalase C (in rice) and Catalase 3 (in Arabidopsis) on the plasma membrane, respectively. Therefore, it is possible that the VAMP711 protein could be translocated to the plasma membrane through certain unclear mechanisms or under certain physiological conditions.…”
Section: Discussionmentioning
confidence: 99%